2020
DOI: 10.3390/biom10101406
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin Represses Epithelial to Mesenchymal Transition Process Through Modulating Wnt/β-Catenin Signaling Cascade

Abstract: Corilagin (CLG), a major component of several medicinal plants, can exhibit diverse pharmacological properties including those of anti-cancer, anti-inflammatory, and hepatoprotective qualities. However, there are no prior studies on its potential impact on the epithelial-to-mesenchymal transition (EMT) process. EMT can lead to dissemination of tumor cells into other organs and promote cancer progression. Hence, we aimed to investigate the effect of CLG on EMT and its mechanism(s) of action in tumor cells. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The polymerization is associated with the formation of flat, sheet-like membrane protrusions called lamellipodia, or finger-like extensions at the edge of lamellipodia called filopodia [ 19 ]. In lamellipodia, actin filaments are arranged in a loosely organized meshwork, often referred to as dendritic networks [ 20 ], whereas, in filopodia, actin filaments arrange into parallel bundles [ 21 ]. These two different types of organizations rely on the action of specific actin-organizing proteins.…”
Section: Role Of Cellular Cytoskeleton In Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerization is associated with the formation of flat, sheet-like membrane protrusions called lamellipodia, or finger-like extensions at the edge of lamellipodia called filopodia [ 19 ]. In lamellipodia, actin filaments are arranged in a loosely organized meshwork, often referred to as dendritic networks [ 20 ], whereas, in filopodia, actin filaments arrange into parallel bundles [ 21 ]. These two different types of organizations rely on the action of specific actin-organizing proteins.…”
Section: Role Of Cellular Cytoskeleton In Emtmentioning
confidence: 99%
“…This is followed by the degradation of the underlying basement membrane and ECM [ 18 , 19 , 20 ]. The ability to degrade the ECM and invade into the surrounding tissue parenchyma is obtained by activating the EMT program, where the epithelial cancer cells transform into a more invasive and motile mesenchymal state [ 21 , 22 ]. During EMT, adherens junctions’ dissolution is stabilized by the cleavage and degradation of E-cadherin at the cell membrane [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Moreover, to intricate an already debated and complex process, cancer cells are often reported to display different degrees of EMT phenotypes. [38][39][40][41] As reported above, SNHGs exert multiple roles being able to act as molecular sponges for several miRNAs (Figure 2) or binding proteins modulating in that way multiple biological processes, including the EMT in cancer. 28 The known SNHGs in EMT are resumed in Table 2.…”
Section: Small Nucleolar Rna Host Genes In Emt Processmentioning
confidence: 86%
“…Indeed, EMT‐induced cells demonstrate enhanced migration, invasion, and frequently express N‐cadherin at the expense of E‐cadherin reducing in this way the intercellular adhesion 35–37 . Moreover, to intricate an already debated and complex process, cancer cells are often reported to display different degrees of EMT phenotypes 38–41 …”
Section: Small Nucleolar Rna Host Genes In Emt Processmentioning
confidence: 99%
“…Interestingly, the proliferation and metastasis of cancer cells are in close relationship with each other and can trigger chemoresistance [ 239 , 240 , 241 ]. It has been reported that TGF-β can induce EMT in mediating chemoresistance [ 242 , 243 , 244 , 245 ]. miRNA-134/487b/655 stimulates TGF-β-mediated EMT in lung cancer cells.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%